Key Technology in the Design of Double-fed Induction Generator for High Power Wind Turbine - LI Jinze; WANG Jianliang (Kongzhi Yu Xinxi Jishu)
Wind driven DFIG (double fed induction generator) is the mainstream model of grid-connected high power wind turbine and DFIG is the key part that influence the performance and reliability of wind turbine. Key technologies of DFIG such as electromagnetic design, insulation structure, slip ring system and bearing electric erosion have been analyzed and illustrated in this article and some design principles have been presented, which gives new ideas and concepts to improve DFIG design.